Evaluation of POME-biogas production system for eco-efficiency improvement in selected palm oil mills in Malaysia - Wong, Siew Yien (2018)
The release of massive amount of methane gas into the atmosphere from the POME treatment ponds has made many realize that the industry must be sustainable if its national and international market is to be safeguarded. Malaysian palm oil mills have been encouraged to implement biogas facilities in the mills to capture the methane gas and used it for power generation. However, different configurations of biogas capture technology and biogas utilization pathway currently adopted in palm oil mills may lead to a great variance of outcomes from both environmental and economic point of views. This situation could subsequently affect the selection and decision on an appropriate AD system among the palm oil industry players. Therefore, the objectives of this study are 1) to determine the environmental impacts and costs incurred for ecoenvironmental conservation of Malaysian palm oil mills with different POME-biogas systems using Life Cycle Assessment (LCA) and Environmental Life Cycle Costing (ELCC) approach, 2) to evaluate the environmental and economic performance of Malaysian palm oil mills with current POME-biogas production systems, and 3) to develop an improvement assessment model for a better decision making among the palm oil industry players using Eco-costs Value Ratio (EVR) model. From the environmental perspective, 11 impact categories have been determined in palm oil mills using Eco-indicator 99 methodology embedded in an LCA software called SimaPro Version 8.0. Based on the weighted results, respiratory inorganics, climate change and fossil fuels depletion are identified as the most significant impact categories. The impacts that contributed to the first two impact categories are primary derived from the application of chemical fertilizers in plantations and highly dependent on diesel for transportation and machinery both in plantations and palm oil milling processes. As for the fossil fuels depletion impact category, the contributing units to this are believed to be derived from the activities of chemical fertilizers production and transporting of the manufactured fertilizers and fresh fruit bunches (FFBs) from plantation to mill. Meanwhile, the total costs incurred in the palm oil mills with different POME-biogas production systems include fixed costs, depreciation costs and variable costs have been determined and computed. Amongst, production costs for CPO and kernel are identified as the most significant cost components in the capital budgeting analysis. This is believed to be attributed to the low FFB processed and high milling cost. Net present value (NPV), internal rate of return (IRR), benefit cost ratio (BCR) and payback period (PBP) of a financial projection of different biogas systems have been analyzed. The results have revealed that the biogas configuration with AD tank to grid connection system is more financially viable; greater profitability with shorter payback period. Besides, it is also found that the financial projection of each biogas configuration is identically sensitive when the quantity of crude palm oil (CPO) production is decreased, instead of the increment of biogas investment. It is believed that the sustainable supply of FFB from plantations and consistency production of CPO in the mill has a dominant effect on its financial viability. From the eco-efficiency analysis perspective, the results have revealed that palm oil mill with biogas configuration of AD tank to grid connection system has the lowest eco-costs value ratio (EVR) value among the groups; 0.08. Whereas, palm oil mill with biogas configuration of AD tank to co-firing system has showed to have the highest EVR value; 0.31. This also indicated that palm oil mill with biogas configuration of AD tank to grid connection has the highest eco-efficiency and it can be said that it is the most sustainable palm oil mill in terms of environmental and economic aspects. In fact, all palm oil mills are found to be eco-efficiency from environmental and economic point of views due to their low EVR values. Ecoefficiency of all palm oil mills would improve when the green procurements in plantations are taken seriously and the milling technological is revolutionized with advanced technologies. In a nutshell, this finding has proved that Malaysian palm oil mills with biogas facilities are indeed sustainable from environmental and economic aspects. It is also suggested that the adoption of biogas configuration of AD tank to grid connection would lead a positive effect to the palm oil industry in terms of a long run environmental protection and safeguard of economic.